2023
DOI: 10.5398/tasj.2023.46.3.306
|View full text |Cite
|
Sign up to set email alerts
|

Frozen Semen Characteristics of Limousin Bull at Different Ages

A. Baharun,
A. B. Setiawan,
A. Rahmi
et al.

Abstract: Strategies to increase the population and productivity of beef cattle can be implemented through reproductive management, such as artificial insemination (AI) using frozen semen. This study aims to evaluate the characteristics of frozen semen of Limousin bulls of different ages, which can still be used for insemination programs up to 12 years of age. This study used frozen semen of Limousin bulls ages 3, 8, and 12 years produced in 2021 at the Artificial Insemination Center in Singosari, East Java Province, In… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The results of whole plasma membrane analysis showed that Pasundan bulls named Bagaskara and Kartarajasa had lower values ( p < 0.05) compared to other males ( Table 1 ). Baharun et al [18] reported that an IPM plays an essential role in metabolic processes associated with spermatozoa motility and viability, and it is essential for fertilization, fertility, and spermatozoa function for successful AI. Impairment to the plasma membrane can diminish sperm motility, alter spermatozoa morphology and metabolism, and cause an imbalance of intracellular components such that spermatozoa fertility may be compromised.…”
Section: Resultsmentioning
confidence: 99%
“…The results of whole plasma membrane analysis showed that Pasundan bulls named Bagaskara and Kartarajasa had lower values ( p < 0.05) compared to other males ( Table 1 ). Baharun et al [18] reported that an IPM plays an essential role in metabolic processes associated with spermatozoa motility and viability, and it is essential for fertilization, fertility, and spermatozoa function for successful AI. Impairment to the plasma membrane can diminish sperm motility, alter spermatozoa morphology and metabolism, and cause an imbalance of intracellular components such that spermatozoa fertility may be compromised.…”
Section: Resultsmentioning
confidence: 99%